The pros and cons of multiple puncture in percutaneous balloon compression for treatment of trigeminal neuralgia - Sun, Chenglong; Zheng, Wenhao; Zhu, Qiang; Du, Quan; Yu, Wenhua (Frontiers in Neurology, 2022)
ABSTRACT Background: Percutaneous balloon compression (PBC) is an effective and well-established surgery for treating trigeminal neuralgia (TN). A pear-shaped balloon is widely accepted as the gold standard for successful PBC. However, if the initial attempt fails to produce a distinct pear shape, there is no conventional strategy to follow: options include repeating a few days later or repuncturing intraoperatively. Aims: This study aimed to analyze the risk and gain of repuncture in the same PBC surgery for TN treatment. Methods: We performed repuncture after the initial failure to obtain a good pear during the same surgery. Repuncture methods include selecting a more appropriate entry point or better entry angle, locating a stretchy spot around the margin of the foramen ovale (FO) with a trocar, exploring the direction with more resistance using a thin guiding needle and replacing the suregon. We reviewed radiographs and medical records from 79 consecutive PBC cases. The complications and surgical outcomes of one-time success pears and multiple repuncturing pears were compared. Results: In 50% of cases, satisfactory pears were obtained after the first puncture, and in 35% of cases, satisfactory pears were obtained following repuncture. Except for hemihypogeusia, which was significantly more common in multiple puncture cases (P < 0.05), no adverse effects were significantly different between the two groups. The log-rank test of the pain-free rate revealed no statistically significant differences between the two groups (P = 0.129). Conclusion: This study establishes the methods and safety of repuncture in PBC for TN treatment. The operation increases pears and does not cause any serious complications. The surgical outcomes of repuncture pears are almost identical to those of one-time success pears.